Characterizing the dayside magnetosheath using energetic neutral atoms: IBEX and THEMIS observations. Issue 6 (17th June 2013) - Ogasawara, K.; Angelopoulos, V.; Dayeh, M. A.; Fuselier, S. A.; Livadiotis, G.; McComas, D. J.; McFadden, J. P.
Abstract : [1] We report on the time evolution of energetic neutral atom (ENA) emissions measured by the Interstellar Boundary Explorer (IBEX) during instances of compressed and expanded dayside magnetosheath. The ENA observations, taken during the passage of a corotating interaction region on 27 and 28 November 2010, are compared with in situ observations from the Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft. IBEX's field of view (6.5° full width at half maximum) covered a wide region of the dayside magnetosheath for several days, providing continuous information from that region. The high sensitivity and high‐energy resolution of IBEX instruments enabled unprecedented remote‐sensing diagnostics of dayside magnetosheath ENA spectra at energies between 0.1 and 6 keV, which can be directly compared with various upstream parameters. The inferred plasma spectra from ENA observations showed characteristic suprathermal tails described by kappa distributions that correlate well with the solar wind cone angle and are in agreement with in situ observations, suggesting that the shock angle contributed to magnetosheath particle heating. Simultaneous in situ ion measurements in the dayside magnetosheath provided by THEMIS agree reasonably well with IBEX‐inferred spectra, demonstrating synergy between remote IBEX ENA observations (global) and in situ measurements (local) for studying localized magnetospheric processes. Key Points: Direct comparison of ENA inferred spectra and in‐situ observations Showed consistency between IBEX and THEMIS with a variety of upstream conditions Found possible correlation between IMF angle and magnetosheath spectral index